Peran Barang Bukti dalam Sistem Pembuktian pada Perkara Pidana: Studi di Polrestabes Makassar - Suherman, Asep Marsel; Agis, Abdul (CV. Social Politic Genius (SIGn), 2024)
This research aims to identify and analyze the role of physical evidence within the evidentiary system for criminal cases at the Makassar City Police Headquarters, as well as the factors influencing said role. This study falls under the category of empirical legal research, emphasizing field research supported by data and interview results. The research was conducted in the city of Makassar. Research findings indicate that the role of physical evidence in the evidentiary system for criminal cases at the Makassar City Police Headquarters is crucial. Physical evidence is significant in complementing other recognized types of evidence, including witness testimony and the defendant’s statement. Furthermore, three factors associated with the role of physical evidence were identified: the legal substance factor, the legal structure factor, and the legal culture factor. Moreover, these factors were assessed as having a significantly positive influence on the evidentiary system for criminal cases at the Makassar City Police Headquarters. It is hoped that the role of physical evidence will be further strengthened, thereby enabling future improvements in the evidentiary system for criminal cases.